EFEKTIVITAS SARANA DAN JALUR EVAKUASI DARURAT MALL BLOK M PLAZA - Hermawan, Muhammad Erix Ade; Vidiyanti, Christy; Astari, Iin Yuni (Universitas Atma Jaya Yogyakarta, 2020)
Blok M Plaza Mall in the middle of Blok M in South Jakarta, surrounded by various modes of transportation, Blok M Terminal, and Blok M MRT Station, make Blok M Plaza mall as a mall characterized by TOD (Transite oriented development) building. Related to a very strategic location, the Blok M Plaza mall became a mall in Jakarta with a busy number of visitors. The crowd at Blok M Plaza mall was interesting to be investigated to find out the effectiveness of emergency evacuation facilities and routes inside the Blok M Plaza mall. This research was conducted on several main mall floors, namely lower ground, upper ground, 1st floor, 2-5th floor, and 6th floor. The method used uses quantitative methods and refers to evaluative methods. Data collection using observations and questionnaires. Data are juxtaposed to get the results of a comparison between observational data with questionnaire data about visitors' perceptions about the path and emergency evacuation facilities. The results, it was concluded: of the nine aspects used as the object of observation, 53% were effective more than the standard, and 33% were effective according to the reference standard for the effectiveness of the path and emergency evacuation facilities.